Risk management in outdoor and adventure programs : scenarios of accidents, incidents, and misadventures - Attarian, Aram, ....- (Champaign, IL : Human Kinetics, 2012)
Based on real-life experiences, Risk Management in Outdoor and Adventure Programs: Scenarios of Accidents, Incidents, and Misadventures offers both students and professionals practice in applying risk management strategies to situations encountered in outdoor and adventure programs. Written by Aram Attarian, an experienced professor and professional in outdoor and adventure recreation, Risk Management in Outdoor and Adventure Programs presents a systematic model for determining why an incident happened and what could be done to prevent a repeat occurrence. More than 50 real-life scenarios represent various situations encountered in outdoor and adventure programming, such as peanut allergies, bridge jumping, stalking by mountain lions, and lightning strikes. These scenarios offer guidance in analyzing hazardous situations and applying appropriate strategies in safety and risk management. Each scenario is followed by questions that can guide discussion or promote research in concepts or policies that are important to outdoor and adventure programming. Accidents and mishaps are a reality in outdoor and adventure programs. Applying risk management strategies to the scenarios in Risk Management in Outdoor and Adventure Programs gives outdoor adventure leaders increased knowledge of the inherent risks of their profession as well as their legal responsibilities in programming, leadership, and management. This text can help leaders and their participants enjoy safe and successful adventures in the great outdoors.
Includes bibliographical references (p. 131-132).
Keywords: Buitenactiviteiten; Risicobeheersing; Outdoor education; Adventure education; Risk management